Adverse childhood experiences, sleep quality/duration and later-life lower extremity function among older adults in China: evidence from CHARLS - Jiaqiang Xiao; Xiaosheng Dong; Meng Ding; Tao Kong (BMC Psychology)
Abstract Objective This study aimed to explore the relationship between adverse childhood experiences (ACEs), sleep, and lower extremity function in older adults using a nationally representative cohort. Methods This study included 4,439 participants aged 60 years or older (mean age: 67.2 ± 5.7 years) from the China Health and Retirement Longitudinal Study (CHARLS) 2015 national survey and the 2014 Life History Survey. ACEs, sleep duration, and sleep quality were assessed through self-report, and lower extremity function was measured using the Short physical performance battery (SPPB). The relationships between ACEs, sleep, and lower extremity function were analyzed using multivariate linear regression model and restricted cubic splines. Results After adjusting for covariates, older adults with four or more ACEs exhibited worse lower extremity function compared to those with no ACEs (β: -0.175). 6–8 h of sleep was associated with improved lower extremity function (β: 0.119), while good sleep quality was also associated with higher lower extremity function scores (β: 0.177). Age-related differences revealed that the association between four or more ACEs and reduced lower extremity function (β: -0.431) was significant only in individuals aged 70 years and older. In the 60–69 years age group, the sleep duration of 6–8 h was significantly related to better lower extremity function (β: 0.150), however, in those aged 70 years and older, more than 8 h of sleep was associated with poorer function (β: -0.378). Furthermore, good sleep quality was associated with better lower extremity function in individuals aged 70 years and older (β: 0.246). Conclusion ACEs, particularly household mental illness and parental disability, are associated with poorer lower extremity function in older adults. Normal sleep duration and good sleep quality are linked to better lower extremity function and may mitigate the negative effects of ACEs. However, these associations vary by age.